Use of oral cleaning devices and their perceived benefits among Malaysians in Kuala Lumpur and Johor Bahru: An exploratory structured approach - Mitha, Shahid; Elnaem, Mohamed Hassan Abdelaziz; Chandran, Jaganmohan; Rajah, Nishakaran Pushpa; Tay, Yi Fam; Babar, Muneer Gohar; Siddiqui, Mohammad Jamshed Ahmad; Jamshed, Shazia Qasim (Medknow, 2018)
Background and Objectives: Various devices have been used to maintain oral hygiene. These include toothbrush and toothpaste, mouthwash, dental floss, miswak, and toothpick. This study attempts to investigate the use of various oral cleaning devices and their perceived benefits among Malaysians. Methods: A quantitative cross-sectional study conducted in two different cities of Malaysia. A convenience sampling approach was adopted. A total of 787 participants agreed to participate in the current research. A validated questionnaire translated into national language was used for data collection. Statistical Analysis Used: Data analysis was performed using Statistical Package for Social Sciences version 20. Results: About 302 respondents were in the age range of 18 – 25 years old (38.4%). There were marginally more females (55.7%) than males (44.3%). Although 99.9% of the participants used a toothbrush, a significant majority (n = 590, 75%) used more than a single device to maintain their oral hygiene. Only 311 respondents knew that toothpicks were inappropriate to use to remove food between teeth and gums, while a majority (n = 592, 75.2%) did not realize that some mouthwashes can stain the teeth. Less than half (42.1%) knew that improper use of miswak might harm the teeth. Conclusions: Although their oral hygiene behaviors are relatively at a higher level, their perceived oral health benefits did not compare well.